2001
DOI: 10.1002/1521-3757(20010716)113:14<2743::aid-ange2743>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Incorporation of Azobenzenes into Oligodeoxyribonucleotide for Effective Photoregulation of Duplex Formation

Abstract: Various organic molecules have been introduced into oligodeoxyribonucleotides (ODNs) by means of linkers to provide new functionalities. [1] We already reported that the cis 3 trans isomerization of an azobenzene moiety in the side chain of ODNs could reversibly photoregulate the formation and dissociation of its duplex: a trans-azobenzene moiety in the ODN stabilizes the duplex, whereas the cis form destabilizes it. [2] By using this modified ODN as a modulator, a T7 DNA polymerase reaction could also be pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 17 publications
0
16
0
1
Order By: Relevance
“…Synthesis of the modified DNA involving dyes: The modified DNA molecules carrying A , M , N , and S residues were synthesized with an automated DNA synthesizer by using the corresponding phosphoramidite monomer prepared according to previous papers,6, 9, 20 and conventional ones. All the modified DNA molecules listed in Scheme were purified by reversed‐phase HPLC and characterized by MALDI‐TOF mass spectrometry.…”
Section: Methodsmentioning
confidence: 99%
“…Synthesis of the modified DNA involving dyes: The modified DNA molecules carrying A , M , N , and S residues were synthesized with an automated DNA synthesizer by using the corresponding phosphoramidite monomer prepared according to previous papers,6, 9, 20 and conventional ones. All the modified DNA molecules listed in Scheme were purified by reversed‐phase HPLC and characterized by MALDI‐TOF mass spectrometry.…”
Section: Methodsmentioning
confidence: 99%
“…The higher‐temperature, liquid‐crystalline SmC A phase is a fluid phase in which two axially twisted conformers interchange such that the system is either achiral or racemic. Photochromic azobenzenes have been utilized extensively in supramolecular chemistry, catalysis, and materials science because of their efficient, reversible trans – cis photoisomerization, which leads to large changes in molecular geometry 24. It is well known that rod‐like, azo‐containing molecules tend to reorient under linearly polarized light irradiation to the direction perpendicular to the polarization 25.…”
mentioning
confidence: 99%
“…Adjacent to X 1 , an azobenzene residue ( Y D ) was also introduced as the 19th residue. This conjugate of D-threoninol and azobenzene is known to be a good photoswitch of duplex formation [13]. When the corresponding simple acridine-modified DNA 3 is hybridized to the complementary substrate RNA 1 , the target U-19 residue alone remains unpaired, and the 5′-phosphate linkage (indicated by the arrow in Figure 1) of the target is efficiently cleaved by Lu(III) ion in the aid of acid catalysis by the acridine.…”
Section: Resultsmentioning
confidence: 99%
“…The oligonucleotide 9 also bears X 3 and Y D in the middle, but Y D is inserted in the 5′ side of X 3 . A previous study has shown that the steric effect caused by the isomerization of azobenzene strongly depends on the regiochemical conformation of the threoninol backbone [13]. For the purpose of comparison, Y L , a diastereomer of Y D , was prepared and incorporated into oligonucleotides 6 and 7 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation